Partial purification and characterization of alkaline protease enzyme from Pseudomonas aeruginosa for tannery in Bangladesh (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
An extracellular protease producing bacteria was isolated from poultry waste deposited site at Dhamrai, Dhaka. The isolated bacteria was confirmed as Pseudomonas aeruginosa after performing different morphological and biochemical tests The extracellular protease from the isolated P. aeruginosa was partially purified and characterized. The enzyme was purified by ammonium sulphate precipitation and DEAE cellulose column chromatography. SDS-PAGE was performed and the presence of protease enzyme was confirmed and the molecular weight of protease was determined as 66 KDa. Dehairing treatment with the isolated protease enzyme showed higher activity comparing with some available protease of other bacterial sources as well as conventional chemical method. Effect of pH, temperature, salt-ions and other effector molecules on protease from isolated P. aeruginosa was also examined. The enzyme showed higher activity at pH 8.0 and optimum temperature was found as 35-45˚C. The activity of the enzyme slightly decreased in presence of salt-ions (Mg++, Ca++, Zn++, Mn++, Na+, K+) and inhibitors (EDTA, 2-mercaptoethenol, DMSO, SDS, Ethanol, Methanol). The deactivating effect of 2-marceptoethanol indicated the enzyme as cystine protease.Asian Australas. J. Biosci. Biotechnol. 2016, 1 (2), 221-229